Open loop control of the five-axis missile and target flight motion simulator implementation - Kljajić, Nataša D.; Kostić, Miloš I.; Pavić, Miloš V. (Vojnotehnički glasnik / Military Technical Courier, 2015)
An important phase in missile systems development is flight testing and simulation in the environmental conditions dictated by the operation the system is made for. Since field testing of complex systems means a big financial burden and a time consuming process, hardware in the loop (HIL) simulations represent a very effective solution for saving both costs and time. This paper presents an implementation of a control application that integrates synchronized data generation and acquisition on the five-axis missile and target flight motion simulator owned by the HIL laboratory. The described simulation application is a result of a missile development engineer’s need for a simple way to acquire information on a real missile response, when desired control signals are provided. The solution is realized in LabVIEW software using a robust software design architecture named “classic state machine”.
Keywords: tests; simulations; Missiles; Data acquisition; signal generation; state machine; synchronized measurements; hardware in the loop; LabVIEW